Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"–Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Section: 287 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Cinema in Expansion: Challenges and Promises of an Intercultural Relationship - Frey, Aline; Brito, Thaís (Canadian Journal of Film Studies, 2020)
Les auteures dressent le portrait tant des défis actuels que des possibilités qui naissent des relations interculturelles se tissant entre commissaires et cinéastes autochtones et non-autochtones dans le cadre du plus grand festival du film autochtone du Brésil, Cine Kurumin. Ce festival annuel, fondé en 2011, se déroule dans des villages ruraux autochtones, de même que dans des métropoles brésiliennes, attirant ainsi des auditoires variés. Le festival est ouvert aux cinéastes autochtones et non-autochtones qui produisent du matériel audiovisuel portant sur des sujets autochtones de partout dans le monde. Divers processus créatifs y sont encouragés grâce à l’organisation d’ateliers de scénarisation, et des partenariats établis avec des chaînes de télévision permettent une plus large diffusion des films sélectionnés. Alors que les productions audiovisuelles autochtones se développent, leurs contenus se diversifient ; elles englobent en effet de plus en plus de thèmes et de styles, de formats et de perspectives variées. En s’appuyant sur un cadre théorique postcolonial et décolonial, les auteures proposent de nouvelles perspectives sur un cinéma en pleine expansion ; les réalisateurs autochtones et leurs films circulent de plus en plus au sein de festivals non thématiques, reçoivent des prix et font rayonner leurs propres voix et points de vue auprès de publics variés, ce qui crée de nombreuses possibilités d’interactions et de dialogues interculturels. En outre, la mise sur pied de Cine Kurumin témoigne du pouvoir des productions audiovisuelles autochtones de générer des relations interculturelles entre cinéastes, commissaires et public.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; _Nettoyé

Curar el pasado: teoría, curaduría y diálogo en una muestra de arte indígena contemporáneo del Gran Chaco Gualamba - Cantero, Emanuel (Memoria y Sociedad, 2018)
El siguiente artículo es una respuesta a la exposición de arte indígena contemporáneo Gran Chaco Gualamba. Arte, Cosmovisión, Soberanía (Chaco, Argentina; Julio de 2013). Sin desviarse de los propios objetivos de la muestra, problematiza la práctica curatorial como una forma de ver y mostrar a la producción artística de las poblaciones originarias como artefactos significantes íntimamente enlazados con sus formas de vida comunitaria -y no meramente obras de arte autónomas y asépticas de toda función social-. Contrastando las definiciones del equipo de curadoras, el corpus de obras expuestas y el discurso de pobladores originarios, se muestra que este intento por recuperar el nexo orgánico entre arte, cosmovisiones y vida en comunidad resulta trunco, dado que los propios pobladores originarios consideran esta vinculación como una circunstancia históricamente pretérita, previa a los procesos de colonización. Recuperando las luchas presentes de las comunidades, que a falta de ese pasado armonioso plantean su identidad como resistencia necesaria para un futuro distinto – mejor-. This work is a response to a contemporary indigenous art exhibition titled «Gran Chaco Gualamba - Arte, Cosmovisión, Soberanía» (Chaco, Argentina; July 2013). Consistent with the purposes of this exhibition, the article problematizes curatorial practice as a way to present the artistic production of the indigenous populations as significant artifacts intimately involved in the daily community life, and not merely as autonomous artistic objects with no social function. By contrasting the definitions provided by the curatorial team,the corpus of artworks exhibited and the native peoples’ speech, the article shows how the exhibit fails to recover the link between art, cosmovisions and community life because the native populations themselves consider these three spheres as an outdated historical circumstance, previous to the colonization processes. Finally, the current struggles of the communities are mapped which, in the absence of that harmonious past, pose their identity as a necessary resistance for a better future.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Shekuita o el mal trueno: documental performativo, conflictos ontológicos y descolonización de lo real - Rincón, Juan Carlos Valencia; Hoyos, Paula Andrea Restrepo (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
Este artículo analiza las implicaciones ontológicas y el carácter performativo del documental Shekuita o el mal trueno, lanzado en 2017 por un colectivo de producción audio- visual indígena wiwa en la Sierra Nevada de Santa Marta en Colombia. El documental explora las causas, dudas y consecuencias de un triste incidente ocurrido tres años antes: la caída de un rayo sobre una edificación ceremonial de los wiwas, que causó la muerte a casi una docena de líderes. A partir del contraste entre las explicaciones científicas de la tragedia y las que han investigado las autoridades espirituales de la comunidad desde sus ontologías relacionales, y basándonos en un trabajo de campo cuasietnográfico durante el proceso de filmación, buscamos dar cuenta de un caso específico de descolonización de lo real y de los esfuerzos de una comunidad indígena por la libre expresión y la representación autónoma. Encontramos que este documental abre puertas de forma artística a mundos otros, contados en clave insumisa desde una indigenidad que nos interpela. Concluimos que los wiwas performan un realidad que no necesariamente es la que vivieron, sino una que les permite estratégicamente alcanzar más fácilmente la realidad que quieren recuperar. El artículo intenta contribuir a la visibilización de otras ontologías distintas de la naturalista, a mostrar las autocríticas de esta y a manifestar cómo el audiovisual es un espacio propicio para descolonizar lo real. This paper analyzes the ontological implications and the performative nature of the documentary Shekuita o el mal trueno, released in 2017 by a Wiwa indigenous audiovisual production group in Sierra Nevada de Santa Marta, Colombia. The do-cumentary explores the causes, doubts and consequences of a sad incident that happened three years earlier: a lightning strike on a Wiwas ceremonial building, which killed nearly a dozen leaders. Based on the contrast between the scientific explanations of the tragedy and those that the spiritual authorities of the community have investigated according to their relational ontologies and based on a quasi-eth-nographic fieldwork during the filming process, we seek to account for a specific case of decolonization of reality and of the efforts of an indigenous community for free expression and autonomous representation. We find that this documentary opens doors to other worlds in an artistic way, told in an unsubmissive way by an indigenous community that challenges us. We conclude that the Wiwa perform a reality that is not necessarily the one they lived through, but one that strategically allows them to reach the reality they want to recover more easily. The paper at-tempts to contribute to the visibility of other ontologies other than the naturalistic one, to show self-criticism of it and to show how the audiovisual is a propitious space to decolonize reality.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé